Design of theranostic nanomedicine (II): synthesis and physicochemical properties of a biocompatible polyphosphazene-docetaxel conjugate - Jun, Yong Joo; Park, Jung Hyun; Avaji, Prakash G.; Park, Kyung Su; Lee, Kyung Eun; Lee, Hwa Jeong; Sohn, Youn Soo (DOVE MEDICAL PRESS LTD, 2017)
To prepare an efficient theranostic polyphosphazene-docetaxel (DTX) conjugate, a new drug delivery system was designed by grafting a multifunctional lysine ethylester (LysOEt) as a spacer group along with methoxy poly(ethylene glycol) (MPEG) to the polyphosphazene backbone ([NP](n)), and then DTX was conjugated to the carrier polymer using acid-cleavable cis-aconitic acid (AA) as a linker. The resultant polyphosphazene-DTX conjugate, formulated as [NP(MPEG550) 3(Lys-OEt)(AA)(DTX)](n) and named "Polytaxel", exhibited high water solubility and stability by forming stable polymeric micelles as shown in its transmission electron microscopy image and dynamic light scattering measurements. Another important aspect of Polytaxel is that it can easily be labeled with various imaging agents using the lysine amino group, enabling studies on various aspects, such as its organ distribution, tumor-targeting properties, pharmacokinetics, toxicity, and excretion. The pharmacokinetics of Polytaxel was remarkably improved, with prolonged elimination half-life and enhanced area under the curve. Ex vivo imaging study of cyanine dye-labeled Polytaxel showed that intravenously injected Polytaxel is long circulating in the blood stream and selectively accumulates in tumor tissues. Polytaxel distributed in other organs was cleared from all major organs at -6 weeks after injection. The in vitro study of DTX release from the carrier polymer showed that.95% of conjugated DTX was released at pH 5.4 over a period of 7 days. Xenograft trials of Polytaxel using nude mice against the human gastric tumor cell line MKN-28 showed complete tumor regression, with low systemic toxicity. Polytaxel is currently in preclinical study.
Keywords: POLYMER THERAPEUTICS; CLINICAL-EXPERIENCE; DELIVERY; TUMOR; MICELLES; NANOPARTICLES; FORMULATIONS; TAXOTERE(R); CHALLENGES; RELEASE